Effects of a nutrition education intervention on food-provision managerial decisions in Catalan old age nursing homes. - Beatriz Rodríguez-Sánchez; Isaac Aranda-Reneo; Toni Mora (PLoS ONE)
Introduction Existing research does not provide definitive conclusions on the most effective initiatives for preventing malnutrition among older adult residents in nursing homes. Objective We aimed to assess whether a nutrition education intervention provided to nursing home managers can improve dietary managerial decisions within nursing homes. Methods We performed a multicenter study, where each center was randomized to an intervention or a control group. To ensure homogeneous group representation, we stratified the sample based on the facility size and the availability of kitchen equipment. The baseline survey contained questions related to center characteristics, kitchen size and availability of cooking tools, availability of different daily menu options and the staff working in the kitchen. The follow-up survey included questions about the staff responsible for making nutritional decisions, the degree of food handling, the availability of texture-modification tools, and the residents' satisfaction. We use ordered probit regression models to estimate the effect of the educational intervention on decisions around food management. Results From the 238 nursing homes that responded to the initial survey, 176 were followed-up; 56 were allocated to the intervention group and 120 to the control group. There were 53.32 residents per center among the treated group and 40.82 residents in the non-treated institutions. The intervention increased by 24% the nursing homes' probability of increasing their stock of texture-modification tools, which rose to 26% after controlling for the effect of receiving specific training on textures or presentation, compared to the control group. Conclusions The intervention improved managerial decisions in nursing homes concerning meal presentation through an increase in the number of cooking tools. Incorporating structured and comprehensive sessions to improve food texture and presentation could help fight the risk of residents' malnutrition.